Hellenic Theology at the End of the Late Classics - Vyacheslav M. Naidysh (RUDN Journal of Philosophy, 2025)
The sunset of the late classics (second half IV century BC) is a time of crisis of the polis lifestyle, the way out of which was found in the transition from a “small cozy polis” to huge multi-ethnic multicultural empires, which was accompanied by profound transformations of spiritual culture and religious consciousness. In the new socio-political reality, where social relations mediated in space and time dominate, the system of consciousness is becoming more complicated. The areas of personal and social needs are divided, political particularism gives way to motives of ethnointegration, cosmopolitanism, the individual has the opportunity to delve into his own personality, the world of human feelings is enriched, the role of moral self-regulation increases, spiritual culture differentiates into elite and mass, actively reproducing a mystical worldview. With the increasing complexity of the thinking system, the process of cognition rises to a theoretical level. The cognitive and value-semantic components of the cognitive process are separated, which in theology manifested itself in the formation of two approaches. The first one is aimed at searching for generalized meanings expressing the relations of the profane and sacred worlds, in the lifestyle and actions of a person. He was represented by the so-called Socratic schools (Cynics, Cyrenaics, Megarian school, etc.). The history of these schools has shown that such meanings are not expressed by generalizing the experience of individualized personality sensuality. Cultural and historical experience is needed here, which was realized as the need to give cosmic meaning to mental constructions. Therefore, the Cynics evolve towards Stoicism, the Cyrenaics towards Epicureanism, and the Megarians towards Neoplatonism. The second approach (the construction of “authentic divinity”, a conceptual model of the sacred world) was developed by Aristotle. He integrates ontology, cosmology and theology on the basis of the extremely abstract concept of God - the only, eternal, immobile, indivisible, incorporeal, not set in motion by anything else, the beginning of all beginnings and the cause of all causes, a pure theorist and a perfect philosopher contemplating his own thinking. At the same time, Aristotelian theology is not devoid of residual elements of unreflected subjectivity (mythologism, hylozoism, ethical and aesthetic features), which further opened up the possibility of its synthesis with the theologies of the Abrahamic religions, formed on the abstract-conceptual reconstruction of the Old and New Testament mythologies.